ANALISA RASIO UNTUK MENGUKUR KESEHATAN USAHA PADA KOPERASI WANITA “AMIRAH MANDIRI” DI KABUPATEN SITUBONDO - Anik Sudarismiati; Eka Puji Lestari (Growth, 2019)
The research objective is to determine the financial performance of the "Amirah Mandiri" Women's Cooperative in Situbondo Regency, 2014-2018 Period. Data used in the Balance Sheet and Income Statement. The results of the study are (1) Capital Ratio from 2014-2018 namely Unhealthy from the time series and the requested Operational Standards increased. (2) Productive Asset Quality Ratio Healthy Productive Active Quality Ratio from the time series and from the Cooperative Operational Standards is quite healthy. (3) The management ratios considered discuss General Management, Institutional, Capital Management, Management, Liquidity Management, ie Healthy from the time series and from the Operational Standards Assessment is quite healthy. (4) Unhealthy Efficiency Ratios from the time series and from Operational Standards tend to decrease. (5) Liquidity Ratios from 2014-2018 namely healthy from the time series and Cooperative Operational Standards increased. (6) Independence and questionable ratio of Unhealthy from the time series and from the increased Operational Standards. (7) Identity ratios from 2014-2018, namely the healthy time series and fairly sound Operational Standards.